Wellness of Last Mile School Teachers in the District of Dumarao - April Rose Baes Clarin (President University, 2023)
Being healthy is the definition of wellness. The direction every individual chooses determines the inescapable desire to be in a state of wellness. This study aimed to explore the wellness- issues, concerns, and emerging perspectives among the teachers teaching in the last mile schools in the district of Dumarao using a phenomenological design- a pioneering qualitative venture of the department. Following the analytic method of Ryan & Bernard emerged from the findings, thematic typologies, and referents on the wellness issues, wellness concerns, and emerging perspectives on wellness among the teachers teaching in the last mile schools in the district of Dumarao. The identified wellness issues are personified as emotional well-being, physical dimension, environmental well-being, occupational well-being, and financial well-being, whereas the wellness concerns are thematically labeled as personal safety, school meals, weather condition, and school location. A noteworthy finding is the emerging perspectives on wellness among the teachers teaching in the last mile schools in the district of Dumarao drawn through personifications and typologies from the referents of the significant statements coming from the transcripts of the lived experiences as a flexible schedule, interdependence on one another, simple lifestyle, financial matter, and commitment to service of the participants.